C-terminal domain small phosphatase-like 2 promotes epithelial-to-mesenchymal transition via Snail dephosphorylation and stabilization. Issue 4 (4th April 2018) - Zhao, Yulan; Liu, Jinquan; Chen, Fenfang; Feng, Xin-Hua
Abstract : Abstract : The epithelial-to-mesenchymal transition (EMT) is a cellular reprogramming process converting epithelial cells into mesenchymal cell morphology. Snail is a critical regulator of EMT by both suppressing epithelial gene expression and promoting mesenchymal gene expression. Expression and activity of Snail are tightly controlled at transcriptional and post-translational levels. It has previously been reported that Snail undergoes phosphorylation and ubiquitin-dependent proteasome degradation. Here, we report nuclear phosphatase SCP4/CTDSPL2 acts as a novel Snail phosphatase. SCP4 physically interacts with and directly dephosphorylates Snail. SCP4-mediated dephosphorylation of Snail suppresses the ubiquitin-dependent proteasome degradation of Snail and consequently enhances TGFβ-induced EMT. The knockdown of SCP4 in MCF10A mammary epithelial cells leads to attenuated cell migration. Collectively, our finding demonstrates that SCP4 plays a critical role in EMT through Snail dephosphorylation and stabilization.